2019
DOI: 10.1002/mrc.4925
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of serum in patients with cartilage tumours using 1H‐NMR spectroscopy: A pilot study

Abstract: Cartilage‐forming lesions include tumours that can vary in severity from benign enchondromas to high‐grade malignant chondrosarcomas. Chondrosarcoma is the second most frequent malignant bone tumour, accounting for 20–30% of all malignant bone neoplasms. Surgery is the standard treatment for cartilage tumours (CTs); however, their incidental diagnosis and the difficult differentiation of low‐grade lesions like chondrosarcoma grade I from benign entities like enchondroma are challenges for clinical management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The serum profile showed an increased concentration of cystine and 2-hydroxybutyrate and decreased levels of malate and dodecanoic acid for osteosarcoma as well as for the benign tumors, but significance for the latter was low because just one sample of each was used. The metabolic profile of cartilage tumors (CTs) was improved in an NMR study of serum from patients affected by enchondromas and chondrosarcomas (three each) [ 172 ], showing a strong association with the dysregulation of taurine and hypotaurine metabolism as well as the synthesis and degradation of ketone bodies.…”
Section: Metabolite Biomarkersmentioning
confidence: 99%
“…The serum profile showed an increased concentration of cystine and 2-hydroxybutyrate and decreased levels of malate and dodecanoic acid for osteosarcoma as well as for the benign tumors, but significance for the latter was low because just one sample of each was used. The metabolic profile of cartilage tumors (CTs) was improved in an NMR study of serum from patients affected by enchondromas and chondrosarcomas (three each) [ 172 ], showing a strong association with the dysregulation of taurine and hypotaurine metabolism as well as the synthesis and degradation of ketone bodies.…”
Section: Metabolite Biomarkersmentioning
confidence: 99%
“…The identification of disease markers in a biofluid not only offers practical clinical information concerning the risk, diagnosis, and/or prognosis of the disease [ 11 , 12 ] but also detects altered metabolic pathways that could lead to a better understanding of the disease and/or to select a plausible target for a therapy. Some successful examples in which NMR metabolomics has proven useful in the detection of disease biomarkers include cancer [ 12 , 13 ] including colorectal cancer, [ 14 ], IBD [ 15 17 ], CD [ 18 , 19 ], and UC [ 19 ] just to refer to some recent studies. Moreover, it can replace invasive diagnostics such as colonoscopy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These features make metabolomics an important tool to assess the patients’ phenotypes and it has already been widely used to identify diagnostic cancer signatures and prognostic biomarkers [ 22 , 23 , 24 , 25 ]. However, only a few metabolomics studies have been reported for sarcoma and they mainly regard in vitro investigations [ 26 , 27 ]; those performed in a clinical setting were focused on specific sarcoma subgroups [ 28 , 29 , 30 ] and limited only to gemcitabine treatment [ 31 ]. In this prospective study, we used a metabolomics approach to search for new serum prognostic markers for overall survival in patients with metastatic STS treated with trabectedin.…”
Section: Introductionmentioning
confidence: 99%